Endogenous adenosine and adenosine receptors localized to ganglion cells of the retina. - Braas, K M (1987)
Using specific sensitive antisera against adenosine, we have immunocytochemically localized endogenous adenosine to specific layers of rat, guinea pig, monkey, and human retina. Highest adenosine immunoreactivity was observed in ganglion cells and their processes in the optic nerve fiber layer. Substantial staining was also found throughout the inner plexiform layer and in select cells in the inner nuclear layer. Adenosine A1 receptors, labeled with the agonists L-[3H]phenylisopropyladenosine and 125I-labeled hydroxy-phenylisopropyladenosine, were autoradiographically localized. The highest levels of binding sites occurred in the nerve fiber, ganglion cell, and inner plexiform layers of the retina in all the species examined. The distribution of adenosine A1 receptor sites closely parallels that of retinal neurons and fibers containing immunoreactive adenosine. These results suggest a role for endogenous adenosine as a coneurotransmitter in ganglion cells and their fibers in the optic nerve.